(untitled) (Hekima Review, 2014)
In this largely conceptual paper, I seek to establish and discuss the relationship between human security and development. I will then relate the discussion to a particular human security issue, that of health security, focusing primarily on the current Ebola epidemic. I will situate the epidemic within the context of development, and discuss the ways in which it interacts with other forms of human security. The call of the paper is that Ebola should not simply be framed as a global security threat, but first and foremost as a developmental issue. These two different framings of the epidemic and to diseases afflicting Africa elicit different policy approaches.